2017
DOI: 10.1016/j.bbadis.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA in diabetic cardiomyopathy: From mechanism to intervention

Abstract: Diabetic cardiomyopathy is a chronic and irreversible heart complication in diabetic patients, and is characterized by complex pathophysiologic events including early diastolic dysfunction, cardiac hypertrophy, ventricular dilation and systolic dysfunction, eventually resulting in heart failure. Despite these characteristics, the underlying mechanisms leading to diabetic cardiomyopathy are still elusive. Recent studies have implicated microRNA, a small and highly conserved non-coding RNA molecule, in the etiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 123 publications
2
56
0
5
Order By: Relevance
“…For example, miRNA-21 augments pathological cardiac remodelling by stimulating MAP kinase signalling in fibroblasts [192]. Similarly, miRNAs are differentially regulated in diabetic hearts [85, 126, 178]. One example is miRNA-223, which is upregulated in LV biopsies from T2D patients and regulates GLUT4 expression and glucose uptake [126].…”
Section: Mechanisms Contributing To Myocardial Dysfunction In Diabetimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, miRNA-21 augments pathological cardiac remodelling by stimulating MAP kinase signalling in fibroblasts [192]. Similarly, miRNAs are differentially regulated in diabetic hearts [85, 126, 178]. One example is miRNA-223, which is upregulated in LV biopsies from T2D patients and regulates GLUT4 expression and glucose uptake [126].…”
Section: Mechanisms Contributing To Myocardial Dysfunction In Diabetimentioning
confidence: 99%
“…One example is miRNA-223, which is upregulated in LV biopsies from T2D patients and regulates GLUT4 expression and glucose uptake [126]. As previously reviewed, miRNA expression is altered in rodent models of T1D and T2D [85, 176]. One example of this has been observed in T2D ZDF rats, in which dysregulated miRNA-29 expression is correlated with cardiac structural damage [8].…”
Section: Mechanisms Contributing To Myocardial Dysfunction In Diabetimentioning
confidence: 99%
“…These microRNAs exhibit essential roles in regulating genes related to the aforementioned pathophysiologic pathways of DCM including hypertrophy, apoptosis, and fibrosis. MicroRNA-9, 21, 29, 30d, 34a, 144, 150, 320, and 378 correlated strongly with DCM and could be used as potential serum biomarkers in patients with DCM [131]. Although it is not clear whether exercise can normalize certain microRNAs expression in the myocardium, it is exciting to consider that exercise might be able to restore the expression of some microRNAs through cross-talk effect.…”
Section: Prospective New Biomarkers In Dcmmentioning
confidence: 99%
“…An miRNA is a small ncRNA molecule (containing about 22 nucleotides) found in plants, animals, and some viruses that functions in RNA silencing and posttranscriptional regulation of gene expression. Recently, miRNAs have been identified as a critical element involved in cardiac gene remodelling in diabetic heart . It has been shown that changes in synthesis and specific miRNA levels play a crucial role in the progress of cardiac remodelling and heart failure .…”
Section: The Possible Mechanism Of Lncrna In Dcmmentioning
confidence: 99%
“…Recently, miRNAs have been identified as a critical element involved in cardiac gene remodelling in diabetic heart. 154,155 It has been shown that changes in synthesis and specific miRNA levels play a crucial role in the progress of cardiac remodelling and heart failure. 156 Long noncoding RNAs can be used as a platform for the presentation of miRNAs to RNA binding proteins (RBPs) or mRNAs as intracellular, extracellular, or intercellular transporters.…”
Section: Lncrnas Regulation Relate To the Expression Of Dcm-relatedmentioning
confidence: 99%